Assessment of chronic disease management mode (CDMM) on participants with primary hypertension. Issue 7 (6th May 2021) - Ling, Dan; Wang, Rong; Chen, Qun; Liu, Xinyuan; Qi, Xueli; Chen, Chen; Shi, Xiaoman; Dong, Zhaoheng
Abstract: Objective: Hypertension requires continuous and long‐term care to prevent associated complications. Chronic disease management mode (CDMM) was developed to improve patients' self‐management. We aimed to evaluate quality of care and clinical outcomes of CDMM versus routine care. Methods: 300 patients aged >30 years with primary hypertension were randomly allocated to the CDMM intervention group ( n = 162) or the usual care control group ( n = 138). CDMM comprised nursing consultations, telephone contact, online WeChat link, health education, and appropriate referrals during hospitalisation and after discharge. QLICD‐HY (V 2.0) scale was used to evaluate the quality of life. Care outcomes were biochemical parameters, body mass index, blood pressure levels, waist circumference, psychological indicators and quality of life assessed on admission (baseline) and one month post‐care for both groups. Data were collected and analysed using SPSS 20.0. Results: After one month, the intervention group had 6 mm Hg (95% CI: −5.12 to −9.08) lower SBP and 0.6 mM/L (95% CI: −0.52 to −0.68) lower LDL than the control group. In terms of improvements in BMI, UmAlb or waist circumference, there were no differences between both groups. The intervention group scored better on psychological indicators than controls ( P < 0.05), and scores reflecting social and psychological function in the intervention group were significantly higher than scores at baseline, and higher than scores of controls after one month ( P < 0.05). In the control group, there was no statistically significant difference between the scores at baseline and after one month. Conclusions: Under CDMM hypertension care, improvement of blood pressure and LDL was clinically significant. Intervention care further improves social and psychological function among participants with primary hypertension.